(untitled) (International Journal of Engineering and Computer Science, 2021)
Emerging WSN applications include a wide selection of traditional situations with many nodes. The messages are propagated through intermediate nodes, in order to ensure correct contact between the network nodes with the base station, so that a path has many connexions. Generally speaking, the nodes on the sensor network are distinguished by their minimal resources, so protocols must be used that not only guarantee connectivity but also conserve the most energy while maintaining scalability. Different protocols for routing wireless sensor networks have been suggested, however, reactive routing algorithms have been shown to be energy efficient and adaptable to wireless sensor networks. In this paper, under the OMNeT + + simulation platform, the performance of the reactive protocol will be tested, evaluating different scripts. In contrast to the supplementary responsive protocols stated in literature, the AODV protocol has been selected for supremacy in performance. The following parameters have been evaluated: the transmission rate of packets, average delays, overhead routing and energy usage. The findings show that AODV decreases its efficiency with the growth in the number of nodes. As a result, its usability limits the network scalability and the outcomes demonstration that the spatial distribution of nodes affects protocol performance. The standardised delivery shows the best outcomes for our particular works.